Komunikasi Keprotokolan Dalam Pelaksanaan Upacara Wisuda di Universitas Padjadjaran - Siti Intan Ratna Dewi; Diah Karima Dewi; Marlia Marlia (JCommsci - Journal Of Media and Communication Science, 2020)
Each agency requires a protocol in every event or activity, especially because it involves respect and appreciation for each individual actor or entity involved in an activity. Padjadjaran University as a State University Legal Entity is full of activities and / or activities that are official in nature and are attended by high-ranking government officials and other officials / leaders, both leaders of fellow universities within and / or abroad and non-tertiary institutions which of course has a relationship with Universitas Padjadjaran in an official event. The protocol team routinely carries out preparatory / planning activities and coordinates with various relevant directorates at each event, but obstacles still occur outside the plan. This study was conducted to determine the lack of a protocoler's role in carrying out graduation ceremonies that are carried out routinely as evaluation material. The method used is descriptive statistics using an instrument in the form of a questionnaire. The instrument design is divided into 4 groups of questions related to protocols, namely Protocol Attitude, Layout, Honor, and Ceremony. The survey results from the questionnaire were analyzed using descriptive and comparative analysis resulting in a number of shortcomings in the Ceremonial Procedure that could be seen from the results of respondents' responses which tended to be negative. Therefore, efforts must be made to increase some of the activities in the implementation of the Ceremony at the Graduation Ceremony of the University of Padjadjaran.  Keywords: Protocol Communication, Graduation Ceremony, Universitas Padjadjaran